2019
DOI: 10.1002/ejoc.201900111
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Biphenylene: Synthesis, Reactions and Uses

Abstract: Biphenylene is an antiaromatic compound that has a strained butadiene skeleton that joins two benzene rings. Various methods for synthesizing the biphenylene core have been developed. In addition, the reactivity of biphenylene has attracted much attention because C–C bonds of biphenylene can be cleaved by various organometallic species. Furthermore, the biphenylene motif not only acts as a spacer in a variety of functional molecules, but also serves as a backbone for catalysts and ligands. This minireview summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 96 publications
0
29
0
Order By: Relevance
“…Using the VIST method, it is the purpose of this work to illustrate the concept of Baird aromaticity in a class of PAHs based on the biphenylene motif (see Figure 2). Recently, the biphenylene unit [44] has been considered for molecular conductance [8] and singlet fission [33]. Computational studies on the biphenylene unit integrated into larger PAHs have highlighted its effect on Baird aromaticity [45] and biradical character [46].…”
Section: Introductionmentioning
confidence: 99%
“…Using the VIST method, it is the purpose of this work to illustrate the concept of Baird aromaticity in a class of PAHs based on the biphenylene motif (see Figure 2). Recently, the biphenylene unit [44] has been considered for molecular conductance [8] and singlet fission [33]. Computational studies on the biphenylene unit integrated into larger PAHs have highlighted its effect on Baird aromaticity [45] and biradical character [46].…”
Section: Introductionmentioning
confidence: 99%
“…2). Recently, the biphenylene unit [40] has been considered for molecular conductance [8] and singlet fission [33]. Computational studies on the biphenylene unit integrated into larger PAHs have highlighted its effect on Baird aromaticity [41] and biradical character [42].…”
Section: Introductionmentioning
confidence: 99%
“…Biphenylene and its derivatives offer many applications such as thin films polymer with anomalously high electrical conductivity [17], and the precursor for 2D porous graphene dehydrogenation or biphenylene carbon with intrinsic nonzero gap value and delocalized frontier orbitals that indicate a structure with high electronic mobility [18]. A recent study by Takano et al [19] shows that biphenylene motif can be used in functional materials, namely, it can act as a spacer in a variety of functional molecules and serves as a backbone for catalysts and ligands. Recently, Pagano et al [20] reported that actinide substitution into one of the benzene rings of the biphenylene produces a new, more stable electronic structure whose usefulness led to energy storage applications.…”
Section: Introductionmentioning
confidence: 99%